Metastatic malignant PEComa of the brain: An unusual entity with rare presentation (Indian Journal of Case Reports, 2021)
Perivascular epithelioid cell tumor (PEComa) is an unusual mesenchymal tumor comprised histological and immunohistochemically distinctive perivascular epithelioid cells exhibiting myomelanocytic phenotype. We hereby report the case of a 59-year-old female who presented with sudden headache, vomiting, and transient decreased vision with contrast MRI suggestive of the right occipital mass. Biopsy from the right occipital craniotomy mass was reported as metastatic malignant melanoma. The case was referred to our hospital for review. We considered a differential diagnosis of metastasis from malignant melanoma, poorly differentiated carcinoma, high-grade glioma, PEComa, hemangioblastoma, and high-grade sarcoma. A post-operative whole-body PET/CT scan revealed a metabolically active lesion in the endometrium that seems to be primary. It is suggested to consider PEComa as a differential diagnosis in poorly differentiated malignancy and to evaluate accordingly with appropriate immunohistochemistry markers. This is the third reported case of metastatic malignant PEComa to the brain as per the English literature.